Recycling channel selection and financing strategy for capital-constrained retailers in a two-period, closed-loop supply chain - Zhang, Weisi; Zhang, Tao (Frontiers in Environmental Science, 2022)
This paper studies a two-period closed-loop supply chain with the manufacturer or retailer recycling. We establish a model analysis framework to analyze pricing optimization strategy and channel mode selection of electric vehicle batteries. Consider manufacturer recycling (MR) and retailer recycling scenarios. When the retailer recycles, the retailer is restricted by capital due to the need to pay for the construction of the recycling channel. For this reason, the retailer considers bank loans (RRB) or trade credit financing from the manufacturer (RRM). We give the optimal equilibrium strategies under the three modes and compare the recycling and financing modes. The effects of value preference rate and recycling rate of remanufactured products on supply chain profits, product demand, and model selection are analyzed through numerical examples. The results show that the product demand in the first and second periods promotes each other through the recycling rate. The manufacturer does not recycle when the consumer preference rate for remanufactured products falls below a threshold, and capital-constrained retailer is encouraged to recycle through bank financing. The retailer's profit maximizes with manufacturer recycling for arbitrary recycling and remanufactured costs. When the recycling rate is low or high, the capital-constrained retailer chooses bank financing for recycling. When the recycling rate is high, consumer preference for remanufactured products is low, or consumer preference for remanufactured products is exceptionally high, the retailer will choose to recycle and obtain trade credit financing from the manufacturer.